Predicting New-Onset Atrial Fibrillation in Patients with Coronary Artery Bypass Graft: the Precise-Dapt Score - Uğur Küçük; Serpil Şahin (National Scientific Medical Center, 2024)
Aim: Postoperative new-onset atrial fibrillation (POAF) after isolated coronary artery bypass graft surgery (CABG) is associated with adverse events. The Predicting bleeding complications in patients undergoing stent implantation and subsequent dual antiplatelet therapy (PRECISE-DAPT) score is used to predict the bleeding risk after dual antiplatelet therapy and has been associated with arrhythmias in recent years. Therefore, the present study sought to investigate the association between the PRECISE-DAPT score and POAF after coronary artery bypass graft surgery. Materials and Methods: 350 patients who underwent CABG were retrospectively screened. After exclusion criteria, 135 patients were included in the study. A total of 135 patients who underwent on-pump CABG were divided into two groups: patients with POAF and those without POAF. The PRECISE-DAPT score was calculated for each patient, and intergroup comparisons of the calculated scores were performed. Results: POAF was detected in 66 patients out of 135. Patients with POAF had longer hospital stays. PRECISE-DAPT score was higher in the patients with POAF compared to the patients without POAF (p<0.001). PRECISE-DAPT score was determined to be a predictor of POAF after CABG (odds ratio [OR]: 1.305; 95% confidence interval [CI]: 1.268-2.030; p<0.001). The PRECISE-DAPT score for POAF risk had a sensitivity of 60% and a specificity of 79% at cut-off values of 14.5 and above. Conclusion: An increased PRECISE-DAPT score may be used as a predictive score for POAF that may develop during hospital stay after on-pump CABG.